2008
DOI: 10.1063/1.2844282
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of creation and of thermal annealing of light-induced defects in microcrystalline silicon solar cells

Abstract: Single-junction microcrystalline silicon ͑ c-Si: H͒ solar cells of selected i-layer crystalline volume fractions were light soaked ͑AM1.5, 1000 h at 50°C͒ and subsequently annealed at increasing temperatures. The variations of subbandgap absorption during light soaking and during thermal annealing were monitored by Fourier transform photocurrent spectroscopy. The kinetics were shown to follow stretched exponential functions over long times such as 1000 h. The effective time constants appearing in the stretched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In the literature, several studies have observed this peak during SERS measurements in a PDMS device; the most convincing identity of this peak is mono- or poly-crystalline silicon. 35,36 For SERS measurements in the flexible SERS sensor, a silicon wafer was always present underneath the flexible SERS devices during measurements to better visualize the channels, which may have led to the sharp Raman peak. Another possibility is that the reactive ion etching chamber is frequently used for silicon etching, and a silicon wafer was present in the chamber during etching of the flexible SERS PDMS layer; as such, the Au nanoparticles may have been exposed to silicon during the etching process.…”
Section: Methods and Experimental Setupmentioning
confidence: 99%
“…In the literature, several studies have observed this peak during SERS measurements in a PDMS device; the most convincing identity of this peak is mono- or poly-crystalline silicon. 35,36 For SERS measurements in the flexible SERS sensor, a silicon wafer was always present underneath the flexible SERS devices during measurements to better visualize the channels, which may have led to the sharp Raman peak. Another possibility is that the reactive ion etching chamber is frequently used for silicon etching, and a silicon wafer was present in the chamber during etching of the flexible SERS PDMS layer; as such, the Au nanoparticles may have been exposed to silicon during the etching process.…”
Section: Methods and Experimental Setupmentioning
confidence: 99%
“…It is well known that a light‐induced degradation (LID; Staebler–Wronski effect ) issue exists in amorphous silicon (a‐Si:H) thin‐film solar cells, which leads to a reduction of conversion efficiency to a low and stabilized one. By contrast, the microcrystalline silicon solar cell (µc‐Si:H) shows a very mild LID rate of 5% or less and is considered to be of great importance for technological application. It is even reported that the µc‐Si:H solar cells show almost no LID .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that, even if mc-Si:H cells with a high crystalline volume fraction of the i-layer (460%) are more stable, their initial and light-soaked values of (0.8 eV) will be larger than those of cells with medium crystallinity. The kinetics of light-induced degradation in mc-Si:H was recently studied to gain further insight into the exact microscopic mechanism behind this degradation effect [80]. It was demonstrated that, similarly to a-Si:H, both the kinetics of defect creation and annealing could be fitted with stretched exponential functions, as used in the dispersive model mentioned earlier.…”
Section: Philosophical Magazinementioning
confidence: 99%